Without God : Michel Houellebecq and materialist horror - Betty, Louis (University Park, Pennsylvania : The Pennsylvania State University Press, 2016)
"Addresses the religious, metaphysical, and existential dimensions of French novelist Michel Houellebecq's work. Argues that Houellebecq is the foremost contemporary chronicler of the spiritual anxieties of Western and specifically French modernity"--Provided by publisher.
Introduction : the Houellebecquian worldview -- Materialism and secularism -- The future of religion -- Religion and utopia -- Materialist horror -- Liberalism is God and the West is its prophet.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (EBSCO, viewed June 28, 2016).
English.
Keywords: Houellebecq, Michel -- Criticism and interpretation; Houellebecq, Michel; Religion in literature; Materialism in literature; Materialism in literature; Religion in literature; LITERARY CRITICISM -- European -- French; French Literature; Romance Literatures; Languages & Literatures; Criticism, interpretation, etc; Electronic books